Age and growth of the mutton hamlet Alphestes afer, with a review of the size and age of sex change among epinephelids. Issue 1 (13th April 2016) - Marques, S.; Ferreira, B. P.
Abstract : This paper presents results on the age, growth and population structure of a small grouper, the mutton hamlet Alphestes afer, and discusses the observed size and age structure patterns in relation to reproductive strategies among the epinephelids. Ages were determined by examination of sectioned otoliths, which showed a distinct pattern of alternating translucent and opaque zones that formed annually, as validated with tetracycline labelling. The von Bertalanffy growth function was adjusted to the length‐at‐age data of the males and females, but no significant differences were observed between the resulting parameters. The females, however, were older at given sizes and attained larger sizes and ages, with a maximum observed longevity of 13 years and a total length ( L T ) of 26 cm, while the males attained maximum longevities of only 10 years and a 22 cm maximum L T . The L T and age range for the sex change was 16–25 cm and 3–11 years. The total mortality rate ( Z ) was estimated to be 0·55 for females and 0·82 for males. With the males younger and smaller than the females, this species differed from the pattern commonly observed for protogynous epinephelids. Males had slower growth after maturation, probably due to energy allocation to sperm production during sexual development. This study shows that demography is an important tool to understand the pathways for reproductive strategies in grouper populations.